Kegagalan sistem perpajakan dalam menekan peredaran rokok ilegal di indonesia - Aulana, Muhammad Saukhan; Salsabila, Aulia; Hardini, Farantika Dwi; Aji, Azahra Wulandari; Putra, Aditya Amarta (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2025)
The circulation of illegal cigarettes in Indonesia is a form of failure in the taxation system, particularly in the management and supervision of tobacco excise. This journal highlights how the complexity of the excise tariff structure, the low fiscal compliance of industry players, and the lack of data integration and digitalisation in tax administration are the main factors causing the widespread practice of illegal cigarettes. The inefficiency of the tax system has created loopholes that are exploited for excise evasion and embezzlement, which has a direct impact on the formation of the tax gap between the potential and realisation of state revenue. Using an empirical juridical approach, this study reveals that the main solution is not solely in the law enforcement aspect, but rather in the need to reform the excise tariff structure, simplify fiscal regulations, increase tax literacy, and optimise technology in supervision. Reorganising the tobacco taxation system is a strategic key to improving fiscal effectiveness and reducing the circulation of illegal products in a sustainable manner.